Macroscopic and spectroscopic investigations on Eu(III) and Cm(III) sorption onto bayerite (β-Al(OH)3) and corundum (α-Al2O3) - Kupcik, Tomas; Rabung, Thomas; Lützenkirchen, Johannes; Finck, Nicolas; Geckeis, Horst; Fanghänel, Thomas (Journal of colloid and interface science, 2016)
The interaction of trivalent Cm and Eu with the aluminum hydroxide bayerite (β-Al(OH)3) and the aluminum oxide corundum (α-Al2O3) was investigated by batch sorption experiments and time resolved laser fluorescence spectroscopy (TRLFS). The experimental methods for both polymorphs show similar pH dependent sorption behavior at trace metal ion concentrations (∼10−7M), i.e. similar Eu sorption edges and nearly identical Cm speciation between pH=3 and 13. In this pH range the Cm aquo ion as well as the Cm(III) surface species surface⋯Cm(OH)x(H2O)5−x (x=0, 1, 2) can be distinguished by TRLFS. The similar sorption data point to a (surface) transformation of the thermodynamically unstable Al2O3 surface into bayerite, in agreement with the similar isoelectric points obtained for both minerals (pHIEP=8.6-8.8). The pH dependent surface charge is most likely due to the protonation/deprotonation of singly coordinated Al-OH surface groups, prevailing on the edge planes of the rod-like bayerite crystals and the surface of the colloidal Al2O3 particles. These surface groups are also believed to act as ligands for lanthanide/actinide(III) surface complexation. In contrast to the similar sorption behavior at trace metal ion concentrations, discrepancies are observed at higher Eu levels. While similar sorption edges occur up to 7×10−7M Eu for corundum, the pH edge on bayerite is gradually shifted to higher pH values in this Eu concentration range. The latter behavior may be related either to the existence of multiple sorption sites with different sorption affinities, or to the influence of an additional amorphous Al-phase, forming in the course of the bayerite synthesis.